2005
DOI: 10.4161/cbt.4.7.1922
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor, trichostatin A, enhances radiation sensitivity and accumulation of gammaH2A.X

Abstract: Histone deacetylase inhibitors have been shown to induce numerous biologic effects including, altering cell cycle distribution, cytostasis and in certain cases apoptosis. Given their ability to disrupt critical biological processes in cancer cells, these agents are emerging as potential therapeutics for cancer. Recently, it has been identified that histone deacetylase inhibitors can also efficiently enhance the radiation sensitivity of cells, both in vitro and in vivo. In this study, we investigated whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 46 publications
5
63
0
Order By: Relevance
“…In mouse xenograft models, the combination of HDACI treatment (MS-275 [42], valproic acid [43], LBH589 [44], LAQ824 [45]and AN-9 [46]) with radiation therapy, results in a greater delay in tumor growth than that accounted for by a simple additive effect of the corresponding individual treatments. HDAC inhibition by LBH589 [44], TSA [47], depsipeptide [48] and SAHA [49] stabilizes and enhances IR-induced phosphorylated histone H2AX nuclear foci, classical markers of DSBs, suggesting that HDACIs inhibit DSB repair and/or render DNA more susceptible to IR-induced damage. HDACIs facilitate radiation-induced killing in tumor cells and at the same time appear to protect healthy tissues from cutaneous radiation syndrome.…”
Section: Sensitization To Exogenous Dna Damage By Hdacimentioning
confidence: 99%
“…In mouse xenograft models, the combination of HDACI treatment (MS-275 [42], valproic acid [43], LBH589 [44], LAQ824 [45]and AN-9 [46]) with radiation therapy, results in a greater delay in tumor growth than that accounted for by a simple additive effect of the corresponding individual treatments. HDAC inhibition by LBH589 [44], TSA [47], depsipeptide [48] and SAHA [49] stabilizes and enhances IR-induced phosphorylated histone H2AX nuclear foci, classical markers of DSBs, suggesting that HDACIs inhibit DSB repair and/or render DNA more susceptible to IR-induced damage. HDACIs facilitate radiation-induced killing in tumor cells and at the same time appear to protect healthy tissues from cutaneous radiation syndrome.…”
Section: Sensitization To Exogenous Dna Damage By Hdacimentioning
confidence: 99%
“…When high concentrations of HDAC inhibitors are used, relatively large dose modification factors (DMF; ratio of radiation doses in HDAC inhibitor treated and untreated cells that result in the same level of cytotoxicity) are achieved (DMFs as high as ~2). 85 It is evident that drug-mediated cell-cycle redistribution, particularly G 1 -phase arrest, inhibition of DNA synthesis and induction of apoptosis are responsible for the radiosensitizing effect at the relatively high inhibitor concentrations. [82][83][84][85] The synergistic effects at HDAC inhibitor concentrations that are not toxic and do not affect cell cycle distribution may, at least in part, be the result of histone-hyperacetylation induced changes in chromatin structure per se.…”
Section: Hdac Inhibitors and Ionizing Radiationmentioning
confidence: 99%
“…85 It is evident that drug-mediated cell-cycle redistribution, particularly G 1 -phase arrest, inhibition of DNA synthesis and induction of apoptosis are responsible for the radiosensitizing effect at the relatively high inhibitor concentrations. [82][83][84][85] The synergistic effects at HDAC inhibitor concentrations that are not toxic and do not affect cell cycle distribution may, at least in part, be the result of histone-hyperacetylation induced changes in chromatin structure per se. 85,93 It has been shown that incubation of cells with HDAC inhibitors prior to irradiation results in increased levels of γH2AX-the phosphorylated form of the histone variant H2A, which forms nuclear foci in response to DNA damage and is a sensitive marker of ionizing radiation induced double strand breaks (DSB) 94,95 -indicating that the change in chromatin conformation results in increased DSB formation.…”
Section: Hdac Inhibitors and Ionizing Radiationmentioning
confidence: 99%
See 2 more Smart Citations